(3EJMGO GdeZQH GdYQHj Hjf OhGaY GdJcGed GdGbJUGOj h GdeYhbGJ GdSjGSjI (B1989 - 2007s - (3UHjMI(B, (3HNhTs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2011)
(3ebGQHI fXQjI deaghe GdJcGed GdGbdjej GdSjGSj h GdJcGed GdGbJUGOj, ebheGJ GdJcGed GdGbJUGOj GdeZGQHj (B: (3GdGYJHGQGJ GdLYQGajI h GdJGQjNjI , GdGecGfjGJ h GdehGQO GdeJGMI aj HdOGf GdeZQH GdYQHj , eHQQGJ GdJcGed, GdeMGhdGJ GdhMOhjI bHd bjGe GJMGO GdeZQH GdYQHj (B: (3GdYed GdhMOhj bHd (B1962 (3hHYO GdGSJbdGd, eHQQGJ h GgOGa bjGe GJMGO GdeZQH GdYQHj (B: (3GdYhGed GdOGNdjI , GdeDTQGJ GdNGQLjI , CgOGa Ohd GdeZQH GdYQHj ef GdJcGed, GdCMcGe GdCSGSjI dGJMGO GdeZQH GdYQHj (B: (3GdXQha GdeMjWI HGYdGf eYGgI eQGcT h GdedGeM GdcHQi dgG , GdWHjYI GdbGfhfjI dGJMGO GdeZQH GdYQHj, Gdgjcd GdJfXjej h GdHfjI GdeDSSjI dGJMGO GdeZQH GdYQHj (B: (3GdgjFGJ PGJ GdWGHY GdSjGSj h GdgjFGJ PGJ GdWGHY GdJbfj, GdgjFI GdbVGFjI, GdCLgRI PGJ GdWGHY GdJNUUj, GJMGO GdeZQH GdYQHj h GdJfSjb GdSjGSj (B: (3GdGJMGO Hjf GdHfGA GdeDSSGJj h GdJYKQ , GdGJMGO h HYV GdbVGjG GdEbdjejI , GdGJMGO h GdTQGcGJ GdZQHjI, GJMGO GdeZQH GdYQHj h GdJcGed GdGbJUGOj (B: (3GdedGeM GdcHQi dGSJQGJjLjI eZGQHjI ddJfejI GdeTJQcI, GdGWGQ GdbGfhfj dYedjI GdJcGed GdGbJUGOj, fJGFL GdYedjI GdJcGedjI h CNjQG eYhbGJ GJMGO GdeZQH GdYQHj h eOGNd GdJaYjds
(3edGMb U(B.419 (3HHdjhZQGajG(B: (3U(B.473-508s
Keywords: (3GdJcGed GdEbJUGOj GdOhdjs; (3GdJcGed GdEbJUGOj(B- (3GdeZQH GdYQHjs